The Integration of Digital Technology in Learning to Enhance Students’ Learning Motivation and Engagement at SDIT Rabbani, Bengkulu City - Fitri Yuniarti; Alexon; Buyung (MODELING: Jurnal Program Studi PGMI, 2026)
The integration of digital technology in education has become an important strategy for improving the quality of learning and addressing the needs of students in the digital era. This study aims to examine the integration of digital technology in learning and its contribution to students’ learning motivation and engagement at SDIT Rabbani, Bengkulu City. The study employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with teachers, and documentation of digital technology use during the learning process. Data analysis involved data reduction, data presentation, and conclusion drawing. The findings indicate that the use of digital technology, including interactive presentations, educational videos, digital learning platforms, and interactive applications, creates a more engaging and varied learning environment. Digital media helps teachers present learning materials more clearly and provides opportunities for students to participate actively in classroom activities. Students demonstrate increased attention, enthusiasm, participation, and willingness to complete learning activities when digital technology is integrated appropriately. Effective implementation requires teachers to possess adequate digital competencies and to select technology based on learning objectives, student characteristics, and available resources. Digital technology integration can support the development of a more interactive, student-centered, and meaningful learning process. The findings suggest that systematic and pedagogically appropriate use of digital technology can contribute positively to students’ learning motivation and engagement at SDIT Rabbani, Bengkulu City.